Antioxidant, Antibacterial, and Cytoprotective Activity of Agathi Leaf Protein. (28th January 2014) - Zarena, A. S.; Gopal, Shubha; Vineeth, R.
Abstract : In the present study a protein termed agathi leaf protein (ALP) from Sesbania grandiflora Linn . (agathi) leaves was isolated after successive precipitation with 65% ammonium sulphate followed by purification on Sephadex G 75. The column chromatography of the crude protein resulted in four peaks of which Peak I (P I) showed maximum inhibition activity against hydroxyl radical. SDS-PAGE analysis of P I indicated that the molecular weight of the protein is ≈ 29 kDa. The purity of the protein was 98.4% as determined by RP-HPLC and showed a single peak with a retention time of 19.9 min. ALP was able to reduce oxidative damage by scavenging lipid peroxidation against erythrocyte ghost (85.50 ± 6.25%), linolenic acid (87.67 ± 3.14%) at 4.33  μ M, ABTS anion (88 ± 3.22%), and DNA damage (83 ± 4.20%) at 3.44  μ M in a dose-dependent manner. The purified protein offered significant protection to lymphocyte (72% at 30 min) induced damage by t-BOOH. In addition, ALP showed strong antibacterial activity against Pseudomonas aeruginosa (20 ± 3.64 mm) and Staphylococcus aureus (19 ± 1.53 mm) at 200  μ g/mL. The safety assessment showed that ALP does not induce cytotoxicity towards human lymphocyte at the tested concentration of 0.8 mg/mL.